Multistep Conformation Selection in Amyloid Assembly - Hsieh, Ming-Chien; Liang, Chen; Mehta, Anil K; Lynn, David G; Grover, Martha A (Journal of the American Chemical Society, 2017)
Defining pathways for amyloid assembly could impact therapeutic strategies for as many as 50 disease states. Here we show that amyloid assembly is subject to different forces regulating nucleation and propagation steps and provide evidence that the more global β-sheet/β-sheet facial complementarity is a critical determinant for amyloid nucleation and structural selection.